High‐efficient xylitol production by evolved Candida maltosa adapted to corncob hemicellulosic hydrolysate. Issue 12 (7th March 2016) - Jiang, Xiaolong; He, Peng; Qi, Xianni; Lin, Yuping; Zhang, Yongkui; Wang, Qinhong
ABSTRACT: BACKGROUND: To compete with chemical hydrogenation, xylitol production by a biotechnological method has to decrease production cost by improving the performance of the strain, using low‐cost substrate and developing a simple and efficient bioprocess. This study attempted to reach high‐efficient xylitol production using cheap substrate. RESULTS: A new evolved strain, Candida maltosa CHH65 showed improved cell growth in corncob hemicellulosic hydrolyzate (CHH) and similar product performance using xylose and CHH as substrate, was developed by serial culture transfer for adapting to CHH and solving the problem of inhibition of CHH. The new strain was recycled at least four times and still produced xylitol. In the test conditions, xylitol concentration reached more than 100 g L −1 within 48 h, with yield > 0.73 g g −1, and productivity > 2 g L −1 h −1 when using CHH as substrate. CONCLUSION: The capability of the xylose‐fermenting C. maltosa to convert CHH to xylitol was greatly enhanced so that the newly developed bioprocess for xylitol production from low‐cost substrate with multiple recycled C. maltosa could be suitable for industrial application and reduce the production cost. © 2016 Society of Chemical Industry